Low temperature isothermal amplification of microsatellites drastically reduces stutter artifact formation and improves microsatellite instability detection in cancer. Issue 21 (17th September 2019) - Daunay, Antoine; Duval, Alex; Baudrin, Laura G; Buhard, Olivier; Renault, Victor; Deleuze, Jean-François; How-Kit, Alexandre
Abstract: Microsatellites are polymorphic short tandem repeats of 1–6 nucleotides ubiquitously present in the genome that are extensively used in living organisms as genetic markers and in oncology to detect microsatellite instability (MSI). While the standard analysis method of microsatellites is based on PCR followed by capillary electrophoresis, it generates undesirable frameshift products known as 'stutter peaks' caused by the polymerase slippage that can greatly complicate the analysis and interpretation of the data. Here we present an easy multiplexable approach replacing PCR that is based on low temperature isothermal amplification using recombinase polymerase amplification (LT-RPA) that drastically reduces and sometimes completely abolishes the formation of stutter artifacts, thus greatly simplifying the calling of the alleles. Using HT17, a mononucleotide DNA repeat that was previously proposed as an optimal marker to detect MSI in tumor DNA, we showed that LT-RPA improves the limit of detection of MSI compared to PCR up to four times, notably for small deletions, and simplifies the identification of the mutant alleles. It was successfully applied to clinical colorectal cancer samples and enabled detection of MSI. This easy-to-handle, rapid and cost-effective approach may deeply improve the analysis of microsatellites in several biological and clinical applications.